Design and production of a mobile geolocation application for hospitals and medical clinics - Gouder ,Hicham; Guedda ,Alla; Ayoub ,Zekri (Université of Eloued جامعة الوادي, 2026)
In regions like El Oued, private medical clinics, healthcare complexes, and hospitals are widespread, attracting patients from both within and outside the state. However, locating these facilities, determining the shortest routes, or finding accurate addresses remains a significant challenge, especially for visitors or those unfamiliar with the area. This difficulty often delays access to timely medical care. To address this issue, we propose the development of a mobile application designed to provide the geographic locations of healthcare institutions in El Oued, with the potential for future expansion to other cities. The app will offer detailed information about these facilities and integrate mapping services to assist users in navigation. By combining real-time location-based services with a user-friendly interface, the ap- plication aims to simplify the process of finding healthcare facilities, improve patient navigation, and enhance overall access to medical services.
Bachelor's thesis in Computer Science
Keywords: Mobile Application; Android; Geolocation; Google Maps.